Pengaruh Destination Image, Social Media Marketing dan Daya Tarik, terhadap Kepuasan Wisatawan Melalui Keputusan Berkunjung (Studi pada Kebun Raya Liwa, Lampung Barat) - Yunada Arpan (Universitas Batanghari Jambi, 2023)
One of the natural tourist destinations in West Lampung regency is the Liwa Botanical Garden (KRL) tourist attraction. Tourists' perception of infrastructure in KRL is felt to still not meet expectations such as the lack of information on the existence of KRL. Measurement of KRL consumer behavior needs to be done to understand consumer perceptions related to visiting decisions and visitor satisfaction. The purpose of the study was to: Calculate the magnitude of the direct and indirect influence of endogenous variables on endogenous variables through intervening variables. Calculation analysis can explain the direct and indirect effect. The two-path equation model uses two substructures, namely substructure 1 with equation Model Y= 0.234X1+0.322X2+0.217X3+ (1 and Substructure model 2 with equation Z= 0,132X1+0,170X2+0,256X3+ Î1.. All partial t-count assays > t-table 1.66 mean a linear relationship occurs between exogenous and endogenous variables. There is simultaneously a linear relationship between exogenous variables to the endogenous variable F-count 22.183 > F-table 2.70. This means that there is a linear relationship between destination image, social media marketing and attraction to visitor satisfaction through the decision to visit the Liwa Botanical Garden attraction. The magnitude of the influence of destination image, social media marketing, attractiveness and visiting decisions on satisfaction was 49.4%, while the rest (100% - 49.4%) = 50.6% was influenced by other factors that were not studied.